Resin composition for improving the performance of tow prepreg for curved hydrogen pressure vessels
Patent Information
- Application Number
- KR1020230166972
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-27
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2043-11-27
Smart Images

Figure 112023132478015-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a resin composition for improving the performance of tow prepreg for a curved hydrogen pressure vessel, wherein a plate-shaped nanopowder (plate-shaped alumina, plate-shaped graphite, boron nitride powder, mica, synthetic fluorophlogopite, silica, bismuth oxychloride, titanium dioxide, mica, silica, alumina, montmorillonite, etc.) is combined with a first epoxy, a second epoxy, a curing agent, and a curing accelerator to form a plate-shaped nanocomposite, thereby complexly extending the gas permeation pathway and thereby lowering the gas permeability. Background Technology
[0002] To ensure the driving range of hydrogen electric vehicles, it is essential to secure a certain level of hydrogen charged into the vehicle, and currently, high-pressure hydrogen storage tanks are installed in a separate, dedicated mounting space.
[0003] To share hydrogen fuel cell vehicle platforms with electric vehicles, it is essential to ensure compatibility by modifying the shape of high-pressure hydrogen storage tanks so that they can be installed in the battery mounting space of electric vehicles. Furthermore, it is crucial to secure new hydrogen storage tanks and systems that can be installed in this space. Currently, hydrogen storage tanks are manufactured with a fixed shape—specifically a specific aspect ratio—which makes installation in the battery mounting space of electric vehicles difficult.
[0004] Since the container shape is uniform, it is necessary to develop small-diameter containers for compatibility with electric vehicle platforms; however, an increase in the number of containers leads to more connection points, which in turn increases the potential for hydrogen leakage. Furthermore, since the container shape is uniform, it is necessary to develop small-diameter containers for compatibility with electric vehicle platforms; however, an increase in the number of containers leads to more connection points, which in turn increases the potential for hydrogen leakage.
[0005] To solve these problems, curved-tube hydrogen storage containers capable of freely changing shape are being developed. The liner of a curved-tube hydrogen storage container must have a curved structure and be freely deformable. It is manufactured with a micro-curved structure to reinforce expansion pressure, but it is difficult to properly adhere the hydrogen container to the surface of the micro-curved structure when using the conventional braiding process, which is used to wind elastic fibers onto the liner.
[0006] Therefore, to wind the surface of a micro-curved structure, the problems of curved tubular hydrogen storage containers are being addressed through Radial winding, Cross winding, Braiding, and filament winding technologies.
[0007] The above process is used to manufacture tow prepregs of carbon fibers that are wound, and a resin composition is required for this purpose. This resin composition must be formed to possess hydrogen gas barrier properties in a curved hydrogen storage container, that is, in a micro-curved structure, and these properties are a key technology for improving the performance of tow prepregs.
[0008] However, currently, resin compositions having hydrogen gas barrier properties for tow prepregs for curved hydrogen pressure vessels have not been developed. Prior art literature
[0009] Korean Patent Publication No. 10-2242337 (April 14, 2021) The problem to be solved
[0010] The present invention has been devised to solve the problems described above.
[0011] One objective is to complexly extend the gas permeation pathway and thereby lower the gas permeability by forming a plate-shaped nanocomposite by combining a first epoxy, a second epoxy, a curing agent, and a curing accelerator with plate-shaped nanopowders (plate-shaped alumina, plate-shaped graphite, Boron Nitride Powder, mica, Synthetic Fluorphlogopite, Silica, Bismuth Oxychloride, Titanium Dioxide, Mica, Silica, Alumina, Montmorillonite, etc.). means of solving the problem
[0013] The resin composition for improving the performance of tow prepreg for a curved hydrogen pressure vessel according to the present invention comprises a plate-shaped nano-composite material including plate-shaped nano-powder (plate-shaped alumina, plate-shaped graphite, Boron Nitride Powder, mica, Synthetic Fluorphlogopite, Silica, Bismuth Oxychloride, Titanium Dioxide, Mica, Silica, Alumina, Montmorillonite, etc.), comprising 2,400 to 4,900 parts by weight of a first epoxy, 600 to 1,230 parts by weight of a second epoxy, 150 to 307 parts by weight of a curing agent, and 60 to 123 parts by weight of a curing accelerator, based on 100 parts by weight of the plate-shaped nano-powder.
[0014] The first epoxy according to the present invention is composed of Bisphenol A type, Bisphenol F type, HBPA type, DCPD Novolac type, Isocyanate modified type, phenoxy resin type, bromine-based type, aminophenol type, phosphorus-based type, TGDDM-based type, TGDDS-based type, etc., and the second epoxy is characterized by being composed of a polyfunctional epoxy such as Phenol Novolac type, Cresol Novolac type, DCPD Novolac type, BPA Novolac type, etc., or an epoxy that can be used in the first epoxy, of a type different from that used in the first epoxy.
[0015] The curing agent according to the present invention is characterized by comprising ethyleneamines, alicyclic amines, aromatic amines, acid anhydrides, amidoamines, and dicyandiamide (DICY).
[0016] The curing accelerator according to the present invention is characterized by comprising DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea).
[0017] The plate-shaped nanopowder according to the present invention is characterized by further including octadecylamine and aminopropyltriethoxysilane for surface modification.
[0018] The plate-shaped nanocomposite according to the present invention is characterized by being dispersed using a High Shear Mixer. Effects of the invention
[0019] The resin composition for improving the performance of tow prepreg for a curved hydrogen pressure vessel according to the present invention has the effect of lowering gas permeability by complexly extending the gas permeation pathway by combining a first epoxy, a second epoxy, a curing agent, and a curing accelerator with plate-shaped nanopowder (plate-shaped alumina, plate-shaped graphite, boron nitride powder, mica, synthetic fluorophlogopite, silica, bismuth oxychloride, titanium dioxide, mica, silica, alumina, montmorillonite, etc.) to form a plate-shaped nanocomposite. Brief explanation of the drawing
[0020] FIG. 1 is a conceptual diagram showing the characteristics of an MMT nanolayer structure in a resin composition for improving the performance of a tow prepreg for a curved hydrogen pressure vessel according to the present invention. FIG. 2 is a conceptual diagram showing the surface opening process in a resin composition according to the present invention. FIG. 3 is a graph showing gas permeability and mechanical properties according to MMT content in a resin composition according to the present invention, FIG. 4 is a table showing the mechanical properties of an MMT composite according to a mixing method in a resin composition according to the present invention, FIG. 5 is a process flowchart showing a process for preparing a test specimen of a resin composition according to the present invention, FIG. 6 is a graph showing the results of the evaluation of curing characteristics according to the MMT content in the resin composition according to the present invention. FIG. 7 is a graph showing the results of evaluating the heat resistance of the resin according to the MMT content in the resin composition according to the present invention. FIG. 8 is a graph showing the apparent density evaluation and impact test results according to the MMT content in the resin composition according to the present invention, FIG. 9 is a graph showing the results of tensile and flexural tests according to the MMT content in the resin composition according to the present invention, FIG. 10 is a graph showing hydrogen permeability according to MMT content in a resin composition according to the present invention. Specific details for implementing the invention
[0021] In order to explain the present invention, the operational advantages of the present invention, and the objectives achieved by the implementation of the present invention, preferred embodiments of the present invention are illustrated below and examined with reference thereto.
[0022] First, the terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention; singular expressions may include plural expressions unless the context clearly indicates otherwise. Furthermore, in this application, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0023] In describing the present invention, if it is determined that a detailed description of related known components or functions may obscure the essence of the invention, such detailed description is omitted.
[0024] First, to ensure the driving range of hydrogen electric vehicles, it is essential to secure a certain level of hydrogen charged into the vehicle, and currently, high-pressure hydrogen storage tanks are installed in a separate, dedicated mounting space.
[0025] To share hydrogen fuel cell vehicle platforms with electric vehicles, it is essential to ensure compatibility by modifying the shape of high-pressure hydrogen storage tanks so that they can be installed in the battery mounting space of electric vehicles. Furthermore, it is crucial to secure new hydrogen storage tanks and systems that can be installed in this space. Currently, hydrogen storage tanks are manufactured with a fixed shape—specifically a specific aspect ratio—which makes installation in the battery mounting space of electric vehicles difficult.
[0026] Since the container shape is uniform, it is necessary to develop small-diameter containers for compatibility with electric vehicle platforms; however, an increase in the number of containers leads to more connection points, which in turn increases the potential for hydrogen leakage. Furthermore, since the container shape is uniform, it is necessary to develop small-diameter containers for compatibility with electric vehicle platforms; however, an increase in the number of containers leads to more connection points, which in turn increases the potential for hydrogen leakage.
[0027] To solve these problems, curved-tube hydrogen storage containers capable of freely changing shape are being developed. The liner of a curved-tube hydrogen storage container must have a curved structure and be freely deformable. It is manufactured with a micro-curved structure to reinforce expansion pressure, but it is difficult to properly adhere the hydrogen container to the surface of the micro-curved structure when using the conventional braiding process, which is used to wind elastic fibers onto the liner.
[0028] Therefore, to wind the surface of a micro-curved structure, the problems of curved tubular hydrogen storage containers are being addressed through Radial winding, Cross winding, Braiding, and filament winding technologies.
[0029] The present invention relates to a composition of a filler for manufacturing a tow prepreg of carbon fiber wound through the above process.
[0030] In particular, the resin composition according to the present invention must be formed to possess hydrogen gas barrier properties in a curved-tube hydrogen storage container, i.e., a micro-curved structure, and this property is a key technology for improving the performance of tow prepreg.
[0031] Hereinafter, a resin composition according to the present invention will be described with reference to the attached drawings.
[0032] The resin composition for improving the performance of tow prepreg for a curved hydrogen pressure vessel according to the present invention comprises a plate-shaped nanocomposite material including plate-shaped nanopowder (plate-shaped alumina, plate-shaped graphite, Boron Nitride Powder, mica, Synthetic Fluorphlogopite, Silica, Bismuth Oxychloride, Titanium Dioxide, Mica, Silica, Alumina, Montmorillonite), as shown in Table 1, comprising 2,400 to 4,900 parts by weight of a first epoxy, 600 to 1,230 parts by weight of a second epoxy, 150 to 307 parts by weight of a curing agent, and 60 to 123 parts by weight of a curing accelerator, based on 100 parts by weight of the plate-shaped nanopowder.
[0033] In the present invention, plate-shaped nanopowders include plate-shaped alumina, plate-shaped graphite, Boron Nitride Powder, mica, Synthetic Fluorphlogopite, Silica, Bismuth Oxychloride, Titanium Dioxide, Mica, Silica, Alumina, Montmorillonite, etc. However, in the embodiments according to the present invention, Montmorillonite (hereinafter referred to as 'MMT') was selected, and the following description will be based on MMT. However, it should be noted that the plate-shaped nanopowder in this specification is not limited to MMT.
[0034] Table 2 below is an example according to the mixing ratio of the resin composition.
[0035] That is, MMT 1,63, 1st epoxy 80, 2nd epoxy 20, curing agent 5, and curing accelerator 2, with an MMT content of about 1.5%. In another example, MMT 3,32, 1st epoxy 80, 2nd epoxy 20, curing agent 5, and curing accelerator 2, with an MMT content of about 3.0%.
[0036] MMT (weight part) YD-128 (weight part) YD011 (weight part) DICY (parts by weight) DCMU (weight part) 100 2,400 ~ 4,900 600 ~ 1,230 150 ~ 307 60 ~ 123
[0037] Epoxy composition Curing agent apparatus MMT content (%) in the mixture 1st Epoxy (YD-128) 2nd Epoxy (YP011) MMT Curing agent (DICY) Accelerator (DCMU) Black 80 20 0 5 2 0 MMT 1.5 80 20 1.63 5 2 1.5 MMT 3.0 80 20 3.32 5 2 3.0
[0038] First, the montmorillonite according to the present invention, i.e., MMT, is a phylosilicate mineral with a nanolayered structure, and the layered structure (about 1 nm thick) consists of stacked layers, and each layer consists of a single OAl-(Mg)O octahedral sheet (about 100 nm × 100 nm, width and length).
[0039] The layered structure of these MMTs consists of various hybrids and composites, and the van der Waals forces and electrostatic forces that hold the layers together can be overcome by appropriate physical and chemical methods. That is, MMT aggregates can dissociate in an aqueous dispersion to reduce the size of the MMT particles, and small MMT particles can be exfoliated to form individual MMT nanolayers. Since these MMT nanolayers have a high aspect ratio and a large surface area as shown in Fig. 1, adding and dispersing the MMT nanolayers into a polymer matrix can produce clay / polymer nanocomposites with significantly improved mechanical and barrier properties.
[0040] As shown in Fig. 2, the surface of pure MMT can be modified by adding octadecylamine and aminopropyltriethoxysilane. In this case, octadecylamine is added in an amount of 15 to 35 wt.% for use as MMT intercalates, and aminopropyltriethoxysilane is added in an amount of 0.5 to 5% to strengthen the interfacial adhesion between MMT and epoxy.
[0041] Figure 3 (a) shows gas permeability according to MMT content, and Figure 3 (b) shows mechanical properties according to MMT content. First, regarding gas permeability according to MMT content, it can be observed that barrier properties improve as the content increases from 0, 1, 2, to 5%, while increasing it to 10% actually causes gas permeability to decrease. Regarding mechanical properties according to MMT content, it can be observed that strength and elongation decrease, while elastic modulus increases as the content increases. In this case, the MMT content can be applied within 3%.
[0042] Therefore, in the present invention, it is preferable to select the MMT content as a mixing ratio of 1.5% to 3.0%.
[0043] In addition, the illustration in Fig. 4 shows the mechanical properties of the MMT composite according to the mixing method. In this case, when high-shear mixing is applied using a high-shear mixer, the water degradation rate is low, uniform dispersion is possible, and a low defect rate is achieved. More specifically, the mixing is carried out by performing a 3-roll mill three times (10 -> 5 -> 1㎛ gap) and applying a high-shear mixer.
[0044] Next, the epoxy resin according to the present invention may include a first epoxy composed of a Bisphenol A type, Bisphenol F type, HBPA type, DCPD Novolac type, Isocyanate modified type, phenoxy resin type, bromine-based type, aminophenol type, phosphorus-based type, TGDDM-based type, and TGDDS-based type, and the second epoxy may include a polyfunctional epoxy of a Phenol Novolac type, Cresol Novolac type, DCPD Novolac type, or BPA Novolac type, or a type different from that used in the first epoxy among the epoxys that can be used in the first epoxy.
[0045] In this embodiment, the first epoxy may be a bisphenol A type YP-128 resin with an epoxy equivalent of 186 to 190 (g / eq.), and it is preferable to be formulated in the range of 2,400 to 4,900 parts by weight.
[0046] In addition, the second epoxy may be composed of a solid bisphenol A type YD011 resin having an epoxy equivalent of 450 to 500, and it is preferable to formulate it in the range of 600 to 1,230 parts by weight, 150 to 307 parts by weight of a curing agent, and 60 to 123 parts by weight of a curing accelerator.
[0047] In addition, the curing agent according to the present invention may be composed of dicyandiamide (DICY). Dicyandiamide curing agents belong to the heat-curing class of latent curing agents; they are solid at room temperature and insoluble in epoxy resins, and are dispersed in epoxy resins in the form of microparticles. Once heated to near the melting point, they initiate a heated reaction, dissolution, and rapid reaction curing. However, dicyandiamide has the major disadvantage of a high curing temperature. Therefore, it is desirable to use dicyandiamide with various accelerators to lower the curing temperature of dicyandiamide, increase the curing speed, and improve compatibility with epoxy resins. Such a curing accelerator may be DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea).
[0048] In addition to dicyandiamide, curing agents include dimethyl dicykan (DMDC), isophoronediamine (IPDA), diethylenetriamine (DETA), triethylenetetramine (TETA), bis(p-aminocyclohexyl)methane (PACM), methylenedianiline (e.g., 4,4'-methylenedianiline), polyetheramines, e.g., polyetheramine D230, diaminodiphenylmethane (DDM), diaminodiphenylsulfone (DDS), 2,4-toluenediamine, 2,6-toluenediamine, 2,4-diamino-1-methylcyclohexane, 2,6-diamino-1-methylcyclohexane, 2,4-diamino-3,5-diethyltoluene, 2,6-diamino-3,5-diethyltoluene, 1,2-diaminobenzene, 1,3-diaminobenzene, 1,4-diaminobenzene, It may be one or more selected from diaminodiphenyl oxide, 3,3',5,5'-tetramethyl 4,4'-diaminobiphenyl and 3,3'-dimethyl-4,4'-diaminodiphenyl, ethyleneamines, alicyclic amines, aromatic amines, acid anhydrides, amidoamines, etc.
[0049] In addition, in addition to DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea), other curing accelerators may include 3-(3,4-dichlorophenyl)-1,1-dimethylurea (3-(3,4-dichlorophenyl)-1,1-dimethyl urea, DCMU), toluene bis(dimethyl urea), U-410M, 1,1'-(4-methylm-phenylene)bis(3,3-dimethyl urea), UR2T), etc.
[0050] Figure 5 illustrates a process for compounding the MMT composite as described above. Specifically, the first and second epoxy are compounded through heating and stirring, and the curing agent and curing accelerator are compounded. In this case, the curing agent is sheared three times with a 3-roll mill before compounding, and when compounding the epoxy and curing agent, high-shear mixing is performed using a high-shear mixer.
[0051] Once the blended resin is completed in this way, the resin characteristics are evaluated before curing, and Neat Resin specimens are fabricated to evaluate their physical properties.
[0052] First, Table 3 and Figure 6 show the results of the resin property evaluation before curing. According to these results, as the MMT content increases, the curing speed is delayed and the curing heat decreases. Additionally, it can be confirmed that the addition of MMT does not affect the resin curing type. The test equipment used was the TA Instrument DSC2910 (10℃ / min Scan).
[0053] Resin On Set Temp.(℃) Peak Temp.(℃) Heat of RXN(J / g) Black 147.08 156.06 234.3 MMT 1.5 148.79 159.30 193.0 MMT 3.0 151.16 161.97 177.2
[0054] Table 4 and Figure 7 show the results of the heat resistance evaluation of the resin. ASTM D7028 was applied, and a TA Instrument DMA850 (Dual Cantilever Mode, 10Hz, 10㎛ Amplitude, 3℃ / min Ramp, Scan) was used.
[0055] It can be confirmed that the addition of MMT does not affect the heat resistance of the resin.
[0056] Resin Tg(℃) E′onset Peak Tan δ Black 136.28 161.30 MMT 1.5 130.95 160.40 MMT 3.0 144.01 164.00
[0057] Table 5 and Figure 7 (a) show the evaluation results for the apparent density of the resin after curing. The ASTM D702 water displacement method was applied, and Ohaus XPS233 was used.
[0058] It can be confirmed that the apparent density of the resin increases as the MMT content increases.
[0059] Resin Relative density (g / cc, average of 2) Black 1.194 MMT 1.5 1.212 MMT 3.0 1.224
[0060] Table 6 and Figure 7 (b) show the results of the Neat Resin impact test. ASTM D256 was applied, and an Anytester AT-422DA (2.65J Pendulum) was used.
[0061] It can be observed that impact strength decreases as the MMT content increases. This indicates that the resin becomes brittle.
[0062] Resin Impact Strength(kJ / m 2 ) AVE. STDV Black 4.02 0.625 MMT 1.5 2.48 0.139 MMT 3.0 2.06 0.114
[0063] Table 7 and Figure 9 (a) show the results of the Neat Resin tensile test. ASTM D638 was applied, and an Instron 5567, 2mm / min Clip-on Extensometer (Gauge Length 25mm) was used.
[0064] It can be observed that as the MMT content increases, strength and elongation decrease, while the elastic modulus increases.
[0065] Resin Tensile Strength (MPa) Tensile Modulus(GPa) Elongation @ Break(%) AVE. STDV AVE. STDV AVE. STDV Black 69.67 4.81 3.04 0.74 2.23 0.45 MMT 1.5 54.56 10.71 3.17 0.04 1.83 0.44 MMT 3.0 47.14 7.65 3.17 0.04 1.51 0.31
[0066] Table 8 and Figure 9 (b) show the results of the Neat Resin bending test. ASTM D790 was applied, and an Instron 5567 (5 mm / min) was used.
[0067] It can be observed that as the MMT content increases, strength and elongation decrease, and the elastic modulus increases, similar to the tensile test.
[0068] Resin Flexural Strength (MPa) Flexural Modulus (GPa) Flexural Strain(%) AVE. STDV AVE. STDV AVE. STDV Black 103.59 25.59 3.46 0.04 3.23 0.98 MMT 1.5 88.96 30.16 3.71 0.03 2.57 1.01 MMT 3.0 77.40 21.65 3.63 0.04 2.22 0.68
[0069] Finally, Table 9 and Figure 10 show the results of the H2 gas barrier characteristic evaluation for Neat Resin. ASTM D256 was applied, and PermTech PermeH2 (temperature: 25℃, humidity: 40%, pressure: 1 bar, permeate gas H2) was used.
[0070] It can be confirmed that H2 gas barrier characteristics improve as the MMT content increases. That is, in the absence of MMT, the hydrogen permeability is 95.16 cm. 3 / (m 2 ·24h) or, in the case of MMT 1.5, 90.08 cm 3 / (m 2 ·24h), in the case of MMT 3.0, 88.80 cm 3 / (m 2 It can be confirmed that hydrogen permeability is improved by 24h.
[0071] Resin Hydrogen permeability cm 3 / (m 2 ·24h) Black 95.16 MMT 1.5 90.08 MMT 3.0 88.80
[0072] As described above, the resin composition for improving the performance of tow prepreg for a curved hydrogen pressure vessel according to the present invention can lower gas permeability by complexly extending the gas permeation path by combining montmorillonite, i.e., plate-shaped nanopowder, with a first epoxy, a second epoxy, a curing agent, and a curing accelerator to form an MMT (plate-shaped nano) composite.
[0073] This is because the MMT nanolayer structure has a high aspect ratio and a large surface area, as shown in Figure 1 (b). Therefore, by adding and dispersing the MMT nanolayer into a polymer matrix, it is possible to form an MMT composite with significantly improved mechanical properties and, in particular, blocking properties.
[0074] As such, the present invention has been described with reference to an embodiment illustrated in the drawings, but this is merely illustrative, and those skilled in the art will understand that various modifications and equivalent alternative embodiments are possible therefrom.
[0075] Therefore, the true technical scope of protection of the present invention should be determined by the technical concept of the appended claims.
Claims
Claim 1 A resin composition for improving the performance of tow prepreg for a curved-tube hydrogen pressure vessel comprises a plate-shaped nanocomposite containing surface-modified montmorillonite, and, based on 100 parts by weight of the montmorillonite, 2,400 to 4,900 parts by weight of a first epoxy, 600 to 1,230 parts by weight of a second epoxy, 150 to 307 parts by weight of a dicyandiamide curing agent, and 60 to 123 parts by weight of a DCMU curing accelerator, wherein the montmorillonite is surface-modified by octadecylamine and aminopropyltriethoxysilane, the plate-shaped nanocomposite is dispersed using a high-shear mixer, and the content of the montmorillonite is 1.5 to 1.5 of the total resin composition A resin composition for improving the performance of tow prepreg for a curved hydrogen pressure vessel, characterized by being 3.0 wt% and formed to lower hydrogen permeability by complexly extending the hydrogen gas permeation path in the fine bending structure of the curved hydrogen storage vessel. Claim 2 A resin composition for improving the performance of tow prepreg for a curved hydrogen pressure vessel according to claim 1, wherein the first epoxy is composed of one or more types selected from the group consisting of Bisphenol A type, Bisphenol F type, HBPA type, DCPD Novolac type, Isocyanate modified type, Phenoxy resin type, Bromine-based type, Aminophenol type, Phosphorus-based type, TGDDM-based type, and TGDDS-based type, and the second epoxy is composed of one or more types selected from the group consisting of polyfunctional epoxy of Phenol Novolac type, Cresol Novolac type, DCPD Novolac type, and BPA Novolac type, or epoxy of a type different from the epoxy that can be used in the first epoxy. Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete
Citation Information
Patent Citations
Epoxy resin composition, prepreg, fiber-reinforced plastic material, and manufacturing method for fiber-reinforced plastic material
KR1020170091639A
Tow prepreg having high impact strength for the filament winding
KR1020220085889A